2014
DOI: 10.2214/ajr.12.9917
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Imaging Quality of Pulmonary 64-MDCT Angiography in Pregnancy and Puerperium

Abstract: We found no significant difference in diagnostic quality of pulmonary CT angiography using MDCT between the study and control groups. The use of MDCT acquisition, faster injection rates, higher contrast medium concentration, and higher trigger levels may decrease the number of nondiagnostic studies in this population. MDCT may be a worthwhile investigation in the majority of pregnant patients with suspected pulmonary embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…that the "normal range" outside of pregnancy cannot be applied to pregnant women (Browne et al, 2014;Hedengran et al, 2016). Hedengran et al (2016) also showed that the Ddimer values in individual healthy pregnant women fluctuated by more than 50% and concluded that they may not be of value in the diagnosis of VTE during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…that the "normal range" outside of pregnancy cannot be applied to pregnant women (Browne et al, 2014;Hedengran et al, 2016). Hedengran et al (2016) also showed that the Ddimer values in individual healthy pregnant women fluctuated by more than 50% and concluded that they may not be of value in the diagnosis of VTE during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of that study hypothesized that the use of multidetector CT, higher contrast concentration, faster injection rates, and higher trigger levels may contribute to the decreased amount of nondiagnostic studies [15].…”
Section: Discussionmentioning
confidence: 99%
“…67 Interestingly, some results suggest that various effects from pregnancy may impact contrast distribution in CTA with a substantially higher rate of technically suboptimal and nondiagnostic scans compared with nonpregnant patients, that is, up to one-third of scans. 78,79 However, others have found no statistical differences, 80 and a recent meta-analysis found comparable pooled rates of nondiagnostic scans between CTA and V/Q scintigraphy, that is, 12.5 versus 11.5%. 81 It is worth noting that these results on V/Q scans are from planar studies, and the studies on Q SPECT and Q SPECT/CT included in our meta-analysis substantiate the potential of perfusion-only scans in selected groups, for example, pregnant patients.…”
Section: Pulmonary Embolism Imaging In Pregnancymentioning
confidence: 99%